Analisis Fitokimia, Aktivitas Antioksidan dan Toksisitas Ekstrak Metanol Daun Kucai (Allium schoenoprasum) secara In Vitro - Tanowijono, Gabriella Frederica; Hendrawan, Siufui; Ferdinal, Frans (Universitas Medan Area, 2025)
The development of degenerative diseases is influenced by oxidative stress, which stems from an imbalance between free radicals and the body’s antioxidant defenses. Therefore, natural antioxidant supplementation is considered an essential preventive strategy. Chives leaves (Allium schoenoprasum) are functional foods containing various bioactive compounds; however, their potential as natural antioxidants remains underexplored. This study aims to evaluate the antioxidant activity and toxicity profile of the extract through in vitro assays. The extraction process using maceration and percolation techniques with methanol as the solvent. The analytical procedures encompassed phytochemical profiling, quantification of total phenolic compounds using the Folin–Ciocalteu reagent, and antioxidant capacity evaluations utilizing the Ferric Reducing Antioxidant Power (FRAP) and ABTS (2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid)). The resulting total phenolic content of 439.45 μg/mL, equivalent to 14.65 mg gallic acid equivalent (GAE) per gram of dry weight (DW). The IC₅₀ values were 21.93 μg/mL (ABTS) and 13.06 μg/mL (FRAP), indicating strong antioxidant activity. Toxicity assessment using the Brine Shrimp Lethality Test yielded an LC₅₀ value of 333.86 μg/mL, suggesting low toxicity. These results indicate that the extract holds a great promise as a safe and effective source of natural antioxidants.